Manganese zinc ferrite material as well as preparation method and application thereof
By using Fe2O3, ZnO and SnO2 in manganese-zeb ferrite materials to adjust the valley point, the problems of high losses and high costs of existing wide-temperature materials under high frequency and high temperature conditions are solved, and the low loss and low cost material performance is achieved, meeting the needs of charging piles.
Patent Information
- Application Number
- CN202311372390.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
Existing wide-temperature materials have high losses and high costs under high frequency and high temperature conditions, making it difficult to meet the needs of charging piles.
Fe2O3 and ZnO are used as the main material, and an appropriate amount of SnO2 is added, and the valley point of the ferrite material is adjusted through the synergistic action of Fe2O3, ZnO and SnO2. The working temperature reaches 120℃ above 100℃, and no Co2O3 is added to reduce costs.
It achieves low loss at a frequency of 400kHz and a temperature of around 120℃, reduces material costs and meets the needs of fast charging under high current of charging piles.
Smart Images

Figure BDA0004506725690000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of magnetic materials and relates to a manganese-zinc ferrite material and a preparation method and application thereof. Background Art
[0002] At present, wide temperature materials meet the needs of energy conservation and emission reduction policies due to their low loss and wide temperature characteristics. Major companies inside and outside the country have carried out relevant development work, such as Philips' 3C96, 3C95, 3C97, domestic Jianuo's JPP96, Tiantong's TPG33 and other materials. These wide temperature materials are suitable for switching power supplies, chargers and new energy fields. However, since wide temperature materials must be added with Co2O3 or Co3O4, the material cost is relatively high. Moreover, wide temperature materials are currently used more in the 100kHz frequency band. These two points have currently restricted the development of some charging piles. Because the charging pile is working under high current, the operating temperature generally exceeds 100℃ and is around 120℃. The operating frequency is also 400kHz. However, wide temperature materials only focus on a wide temperature range, and the loss of a single temperature point is not as low as the loss of a single material at a valley point.
[0003] CN115650718A discloses a manganese-zinc ferrite material having ultra-wide temperature range, low power consumption and temperature stability of magnetic permeability and a preparation method thereof. The manganese-zinc ferrite material consists of a main component and an auxiliary component; the main component, in terms of molar percentage, includes ferric oxide, zinc oxide, and the rest is manganese oxide; the auxiliary component includes at least 5 of the following raw materials: CaCO3, SiO2, ZrO2, Nb2O5, SnO2, Co3O4. The operating frequency of the material is 100kHz-200kHz, and the loss is 380±10% under the conditions of 100°C, 100kHz, and 200mT.
[0004] CN112573912A discloses a medium-bandwidth MnZn ferrite material with wide temperature and low loss characteristics and a preparation method thereof. The material is composed of Fe2O3, MnO and ZnO as main components and additive auxiliary components, the molar percentage of the main components is: Fe2O3 is 52.5-53.5mol%, ZnO is 8.8-9.8mol%, and MnO is the balance; the content of each component of the additive auxiliary component is: CaCO3 is 0.04-0.06%, Nb2O5 is 0.02-0.03%, Co2O3 is 0.35-0.45%, ZrO2 is 0.01-0.03%, SiO2 is 30-120ppm, wherein the Si element is added in the form of nano-scale aerosolized SiO2, and the 400kHz and 100mT valley points of the material are at 25°C, without taking into account high temperature losses, and are not suitable for charging piles.
[0005] CN114685154A discloses a high-frequency, wide-temperature, ultra-low-loss ferrite material, including a main formula and a dopant formula, wherein the components and proportions of the main formula are: Fe2O3 is 70-72mol%, MnO is 20-22mol%, and ZnO is 6-10mol%. The proportions of each main formula total 100mol%. Relative to the total amount of the main formula, the components and weight percentages in the dopant formula are: CaCO3 is 1-1000ppm, SnO2 is 100-300ppm, Co2O3 is 50-80ppm, Bi2O3 is 50-100ppm, nano-SiO2 is 50-100ppm, and CCTO is 50-100ppm. The operating frequency of the material is 100kHz, and 400kHz is not taken into account. Moreover, the cost is relatively high when Co2O3 is added.
[0006] Therefore, it is necessary to develop a high-frequency, valley-point-around 120°C, and low-cost material to meet the needs of charging piles. Summary of the invention
[0007] The purpose of the present invention is to provide a manganese-zinc ferrite material and its preparation method and application. The present invention uses Fe2O3 and ZnO as the main materials, and adds an appropriate amount of SnO2. The synergistic effect of the three can adjust the valley point of the ferrite material. The working temperature is above 100°C and reaches 120°C, which meets the requirements of efficient charging and reducing the use cost. No Co2O3 is added to achieve the purpose of reducing costs and increasing efficiency. The working frequency is 400kHz, which can meet the needs of fast charging under high current of charging piles.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a manganese-zinc ferrite material, comprising a main material and an additive, the main material comprising Fe2O3, ZnO and MnO, the additive comprising SnO2, taking the total molar amount of the main material as 100%, the molar proportion of Fe2O3 is 52.55-52.75 mol% (for example: 52.55 mol%, 52.6 mol%, 52.65 mol%, 52.7 mol% or 52.75 mol%, etc.), the molar proportion of ZnO is 9.5-10.3 mol% (for example: 9.5 mol%, 9.8 mol%, 10 mol%, 10.1 mol% or 10.3 mol%, etc.), taking the mass of the main material as 100%, the mass of SnO2 is 0.05-0.15% (for example: 0.05%, 0.08%, 0.1%, 0.12% or 0.15%, etc.).
[0010] In the manganese-zinc ferrite material of the present invention, Fe2O3, ZnO and SnO2 are used to simultaneously control the valley point. The valley point of the material is the point where the magnetocrystalline anisotropy constant K1 is 0. This point is obtained by the combined action of ferrite (positive K1 value) and MnZn ferrite (negative K1 value). A part of the Fe2O3 content in the present invention will generate ferrite. Zinc ferrite itself has no magnetocrystalline anisotropy. It adjusts the valley point by adjusting the amount of Fe2O3 and MnO to adjust the amount of ferrite and MnZn ferrite generated to affect the valley point of the material. Sn in SnO2 4+ It will enter the octahedral position and the crystal lattice, which will reduce the magnetocrystalline anisotropy constant K1 value of the main phase MnZn ferrite and play a role in adjusting the magnetocrystalline anisotropy constant.
[0011] Preferably, based on the mass of the main material being 100%, the mass of the ZrO2 is 0.02-0.045%, for example, 0.02%, 0.025%, 0.03%, 0.04% or 0.045%.
[0012] Preferably, based on the mass of the main material being 100%, the mass of CaO is 0.05-0.1%, for example, 0.05%, 0.06%, 0.07%, 0.08% or 0.1%.
[0013] In a second aspect, the present invention provides a method for preparing the manganese-zinc ferrite material as described in the first aspect, the preparation method comprising the following steps:
[0014] (1) After the main material is ground once, it is mixed with glue and spray granulated once, and pre-burned to obtain a pre-burned material;
[0015] (2) The pre-sintered material and the additive material are mixed, subjected to secondary grinding treatment, mixed with glue, subjected to secondary spray granulation treatment, and subjected to pressing and sintering treatment to obtain the manganese-zinc ferrite material.
[0016] The present invention performs pre-sintering by spray granulation once, so that the pre-sintered material is heated more fully and evenly, and the acid radical ions are effectively discharged, which is beneficial to reducing the loss and improving the sintering density of the material. The pre-sintered material is evenly sanded, and the sanding particle size is more even after the second sanding, which is beneficial to forming fine and even grains during sintering and improving the overall performance.
[0017] Preferably, the primary grinding process in step (1) comprises sand grinding.
[0018] Preferably, the ball-water ratio of the primary grinding treatment is 1:(5-8):(0.5-0.6), for example: 1:5:0.5, 1:6:0.55, 1:7:0.6, 1:7:0.5 or 1:8:0.6, etc.
[0019] Preferably, the time of the one grinding treatment is 40 to 80 min, for example, 40 min, 50 min, 60 min, 70 min or 80 min.
[0020] Preferably, the concentration of the glue in step (1) is 7-8%, for example: 7%, 7.2%, 7.5%, 7.8% or 8%, etc.
[0021] Preferably, the mass ratio of the glue to the main material is (8-12):100, for example: 8:100, 9:100, 10:100, 11:100 or 12:100, etc.
[0022] Preferably, the pre-firing temperature in step (1) is 900-950°C, for example, 900°C, 910°C, 920°C, 930°C or 950°C.
[0023] Preferably, the second grinding treatment in step (2) includes sand grinding.
[0024] Preferably, the water ratio of the ball in the secondary grinding treatment is 1:(5-8):(0.4-0.5), for example: 1:5:0.4, 1:6:0.45, 1:7:0.45, 1:7:0.5 or 1:8:0.5, etc.
[0025] Preferably, the secondary grinding treatment time is 40 to 80 min, for example, 40 min, 50 min, 60 min, 70 min or 80 min.
[0026] Preferably, the concentration of the glue in step (2) is 7-8%, for example: 7%, 7.2%, 7.5%, 7.8% or 8%, etc.
[0027] Preferably, the mass ratio of the glue to the total mass of the pre-burned material and the additive material is (8-12):100, for example: 8:100, 9:100, 10:100, 11:100 or 12:100, etc.
[0028] Preferably, the pressing pressure in step (2) is 3-4 MPa, for example, 3 MPa, 3.2 MPa, 3.5 MPa, 3.8 MPa or 4 MPa.
[0029] Preferably, the sintering temperature is 1280-1300°C, for example, 1280°C, 1285°C, 1290°C, 1295°C or 1300°C.
[0030] In a third aspect, the present invention provides a charging pile, which comprises the manganese-zinc ferrite material as described in the first aspect.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention uses Fe2O3 and ZnO as the main materials, and adds an appropriate amount of SnO2. The synergistic effect of the three can adjust the valley point of the ferrite material. The operating temperature is above 100°C and reaches 120°C, which meets the requirements of efficient charging and reducing the use cost. No Co2O3 is added to achieve the purpose of reducing costs and increasing efficiency. The operating frequency is 400kHz, which can meet the needs of fast charging under high current of charging piles.
[0033] (2) The Pcv of the manganese-zinc ferrite of the present invention at 100°C under the conditions of 400kHz 125mT can reach 1155kW / m 3 Below, Pcv at 120℃ can reach 1062kW / m 3 Below 140℃, Pcv can reach 1379kW / m 3 the following. DETAILED DESCRIPTION
[0034] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0035] Example 1
[0036] This embodiment provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0037] (1) a material having a Fe2O3 content of 52.6 mol%, a MnO content of 37.6 mol%, and a ZnO content of 9.8 mol% was sand-milled once, with a material ball-water ratio of 1:6:0.55, sand-milled for 60 min, 10% of glue having a concentration of 7.5% was added, spray granulated, and pre-calcined in a rotary kiln at 920° C. to obtain a pre-calcined material;
[0038] (2) 0.06% CaCO3, 0.04% ZrO2 and 0.1% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:6:0.45, 10% glue with a concentration of 7.5% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 3.5 MPa, and is put into a bell furnace for sintering at 1290° C. to obtain the manganese-zinc ferrite material.
[0039] Example 2
[0040] This embodiment provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0041] (1) a material having a Fe2O3 content of 52.7 mol%, a MnO content of 37.3 mol%, and a ZnO content of 10 mol% was sand-milled once, with a material ball-water ratio of 1:5:0.5, sand-milled for 40 min, 10% of a 7% glue solution was added, spray granulated, and pre-calcined in a rotary kiln at 900° C. to obtain a pre-calcined material;
[0042] (2) 0.1% CaCO3, 0.03% ZrO2 and 0.05% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:6:0.4, 10% glue with a concentration of 7% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 3MPa, and is put into a bell furnace for sintering at 1285°C to obtain the manganese-zinc ferrite material.
[0043] Example 3
[0044] This embodiment provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0045] (1) a material having a Fe2O3 content of 52.55 mol%, a MnO content of 37.15 mol%, and a ZnO content of 10.3 mol% was sand-milled once, with a material ball-water ratio of 1:8:0.6, sand-milled for 80 min, 10% of 8% glue was added, spray granulated, and pre-calcined in a rotary kiln at 900° C. to obtain a pre-calcined material;
[0046] (2) 0.1% CaCO3, 0.045% ZrO2 and 0.15% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:8:0.6, 10% glue with a concentration of 8% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 4MPa, and is put into a bell furnace for sintering at 1295°C to obtain the manganese-zinc ferrite material.
[0047] Comparative Example 1
[0048] This comparative example provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0049] (1) a material having a Fe2O3 content of 52.2 mol%, a MnO content of 38 mol%, and a ZnO content of 9.8 mol% was sand-milled once, with a material ball-water ratio of 1:6:0.55, sand-milled for 60 min, 10% of a glue having a concentration of 7.5% was added, spray granulated, and pre-calcined in a rotary kiln at 920° C. to obtain a pre-calcined material;
[0050] (2) 0.06% CaCO3, 0.04% ZrO2 and 0.1% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:6:0.45, 10% glue with a concentration of 7.5% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 3.5 MPa, and is put into a bell furnace for sintering at 1290° C. to obtain the manganese-zinc ferrite material.
[0051] Comparative Example 2
[0052] This comparative example provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0053] (1) a material having a Fe2O3 content of 53 mol%, a MnO content of 37 mol%, and a ZnO content of 10 mol% was sand-milled once, with a material ball-water ratio of 1:6:0.55, sand-milled for 60 min, 10% of glue having a concentration of 7.5% was added, spray granulated, and pre-calcined in a rotary kiln at 920° C. to obtain a pre-calcined material;
[0054] (2) 0.06% CaCO3, 0.04% ZrO2 and 0.1% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:6:0.45, 10% glue with a concentration of 7.5% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 3.5 MPa, and is put into a bell furnace for sintering at 1290° C. to obtain the manganese-zinc ferrite material.
[0055] Comparative Example 3
[0056] This embodiment provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0057] (1) a material having a Fe2O3 content of 52.6 mol%, a MnO content of 37.6 mol%, and a ZnO content of 9.8 mol% was sand-milled once, with a material ball-water ratio of 1:6:0.55, sand-milled for 60 min, 10% of glue having a concentration of 7.5% was added, spray granulated, and pre-calcined in a rotary kiln at 920° C. to obtain a pre-calcined material;
[0058] (2) 0.06% CaCO3, 0.04% ZrO2 and 0.03% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:6:0.45, 10% glue with a concentration of 7.5% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 3.5 MPa, and is put into a bell furnace for sintering at 1290° C. to obtain the manganese-zinc ferrite material.
[0059] Comparative Example 4
[0060] This embodiment provides a manganese-zinc ferrite material, and the preparation method of the manganese-zinc ferrite material is as follows:
[0061] (1) a material having a Fe2O3 content of 52.6 mol%, a MnO content of 37.6 mol%, and a ZnO content of 9.8 mol% was sand-milled once, with a material ball-water ratio of 1:6:0.55, sand-milled for 60 min, 10% of glue having a concentration of 7.5% was added, spray granulated, and pre-calcined in a rotary kiln at 920° C. to obtain a pre-calcined material;
[0062] (2) 0.06% CaCO3, 0.04% ZrO2 and 0.2% SnO2 are added relative to the total weight of the pre-sintered material, and the pre-sintered material is put into the pre-sintered material for secondary sand grinding, the material ball water ratio is 1:6:0.45, 10% glue with a concentration of 7.5% is added, and spray granulation is performed. The obtained powder is pressed into a standard ring at 3.5 MPa, and is put into a bell furnace for sintering at 1290° C. to obtain the manganese-zinc ferrite material.
[0063] Performance Test:
[0064] The performance of the manganese-zinc ferrite materials obtained in Examples 1-3 and Comparative Examples 1-4 was tested, and the test results are shown in Table 1:
[0065] Table 1
[0066]
[0067] As can be seen from Table 1, from Examples 1-3, the Pcv of the manganese-zinc ferrite of the present invention at 100°C under the conditions of 400kHz 125mT can reach 1155kW / m 3 Below, the Pcv at 120℃ can reach 1062kW / m 3 Below 140℃, Pcv can reach 1379kW / m 3 the following.
[0068] By comparing Example 1 with Comparative Examples 1-2, it can be seen that the molar proportion of iron oxide in the main material of the manganese-zinc ferrite material of the present invention is controlled at 52.55-52.75 mol%, and the performance of the manganese-zinc ferrite material is better. If the proportion of iron oxide is too high, the valley point moves to low temperature and the loss is high. If the proportion of iron oxide is too low, the valley point moves to high temperature and the loss is high. Because only within the above formula range, the material magnetocrystalline anisotropy constant K1 and hysteresis expansion coefficient λ s Only when the iron content is too low or too high will the two increase, thus increasing the loss.
[0069] By comparing Example 1 and Comparative Examples 3-4, it can be seen that the amount of SnO2 added to the manganese-zinc ferrite material in the present invention will affect its performance, and the amount of SnO2 added is controlled to 0.05-0.15% of the mass of the positive electrode material. The performance of the manganese-zinc ferrite material is good. If the amount of SnO2 added is too little, it will not play a role in adjusting the magnetocrystalline anisotropy constant. If the amount added is too much, it will cause lattice distortion, increase internal stress, and worsen loss.
[0070] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A manganese-zinc ferrite material, characterized in that: The manganese-zinc ferrite material includes a main material and an additive, the main material includes Fe2O3, ZnO and MnO, the additive includes SnO2, and based on the total molar amount of the main material as 100%, the molar proportion of Fe2O3 is 52.55-52.75 mol%, the molar proportion of ZnO is 9.5-10.3 mol%, and based on the mass of the main material as 100%, the mass of SnO2 is 0.05-0.15%.
2. The manganese-zinc ferrite material according to claim 1, characterized in that: The additives also include CaO and ZrO2; Preferably, based on the mass of the main material being 100%, the mass of the ZrO2 is 0.02 to 0.045%; Preferably, based on 100% of the mass of the main material, the mass of CaO is 0.05-0.1%.
3. A method for preparing the manganese-zinc ferrite material as claimed in claim 1 or 2, characterized in that: The preparation method comprises the following steps: (1) After the main material is ground once, it is mixed with glue and spray granulated once, and pre-burned to obtain a pre-burned material; (2) The pre-sintered material and the additive material are mixed, subjected to secondary grinding treatment, mixed with glue, subjected to secondary spray granulation treatment, and subjected to pressing and sintering treatment to obtain the manganese-zinc ferrite material.
4. The preparation method according to claim 3, characterized in that: The primary grinding process in step (1) includes sand grinding; Preferably, the ratio of the pellets to water in the first grinding process is 1:(5-8):(0.5-0.6); Preferably, the time for the first grinding treatment is 40 to 80 minutes.
5. The preparation method according to claim 3 or 4, characterized in that: The concentration of the glue in step (1) is 7-8%; Preferably, the mass ratio of the glue to the main material is (8-12):
100.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The pre-firing temperature in step (1) is 900-950°C.
7. The preparation method according to any one of claims 3 to 6, characterized in that: The second grinding process in step (2) includes sand grinding; Preferably, the ratio of the pellets to water in the secondary grinding process is 1:(5-8):(0.4-0.5); Preferably, the secondary grinding process lasts for 40 to 80 minutes.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The concentration of the glue in step (2) is 7-8%; Preferably, the mass ratio of the glue to the total mass of the pre-burned material and the additive material is (8-12):
100.
9. The preparation method according to any one of claims 3 to 7, characterized in that: The pressing pressure in step (2) is 3-4 MPa; Preferably, the sintering temperature is 1280-1300°C.
10. A charging pile, characterized in that: The charging pile comprises the manganese-zinc ferrite material as described in claim 1 or 2.
Citation Information
Patent Citations
Preparation method of medium-broadband wide-temperature low-loss MnZn ferrite material
CN112573912A